PENINGKATAN HASIL BELAJAR SISWA PADA SIFAT LARUTAN GARAM MELALUI PENERAPAN DISCOVERY LEARNING PADA SISWA KELAS XI MIPA-3 - RETNO LUKITASARI (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2021)
This study aims to improve student learning outcomes in class XI MIPA-3 SMAN 2 Jember in the 2017/2018 academic year through the application of discovery learning to the material properties of salt solutions. This research is a Classroom Action Research (CAR) which was conducted in two research cycles, namely cycle I and cycle II. The research subjects were students of class XI MIPA-3 SMAN 2 Jember, totaling 36 students, consisting of 17 male students and 19 female students. Data collection techniques in this study used observation for the implementation of the learning process and tests to determine student learning outcomes. Based on the results of the research, it can be concluded that the application of discovery learning can improve student learning outcomes regarding the properties of salt solutions. In the first cycle the percentage of student learning completeness was 58.33% (21 students) and increased in the second cycle, the percentage of student learning mastery was 88.88% (32 students). There was a significant increase from cycle I to cycle II, namely 30.50%. ABSTRAKPenelitian ini bertujuan untuk meningkatkan hasil belajar siswa kelas XI MIPA- 3 SMAN 2 Jember tahun pelajaran 2017/2018 melalui penerapan discovery learning pada materi sifat larutan garam. Penelitian ini merupakan Penelitian Tindakan Kelas (PTK) yang dilakukan dalam dua siklus penelitian yaitu siklus I dan siklus II. Subjek penelitian adalah siswa kelas XI MIPA-3 SMAN 2 Jember yang berjumlah 36 siswa, terdiri 17 siswa laki-laki dan 19 siswa perempuan. Teknik pengumpulan data pada penelitian ini menggunakan observasi untuk pelaksanaan proses pembelajaran dan tes untuk mengetahui hasil belajar siswa. Berdasarkan hasil penelitan dapat disimpulkan bahwa penerapan discovery learning dapat meningkatkan hasil belajar siswa materi sifat larutan garam. Pada siklus I persentase ketuntasan belajar siswa sebesar 58,33% (21 siswa) dan meningkat pada siklus II, persentase ketuntasan belajar siswa sebesar 88,88% (32 siswa). Terjadi peningkatan yang signifikan dari siklus I ke siklus II yaitu 30,50%.